Efficacy of ultrasound-guided technique for radial artery catheterization in pediatric populations: a systematic review and meta-analysis of randomized controlled trials - Wen Zhang; Kunpeng Li; Hui Xu; Dawei Luo; Changbin Ji; Keshi Yang; Qinghua Zhao (Critical Care, 2020)
Abstract Background The use of an ultrasound-guided technique for radial arterial catheterization has not been well established in pediatric patients. We conducted a systematic review and meta-analysis to evaluate the efficacy of the ultrasound-guided technique for radial artery catheterization in pediatric populations. Method A systematic review of PubMed, Medline, Embase, and the Cochrane library was performed from their date of inception to December 2019. In this meta-analysis, we conducted online searches using the search terms “ultrasonography,” “ultrasonics,” “ultrasound-guided,” “ultrasound,” “radial artery,” “radial arterial,” “catheter,” “cannula,” and “catheterization.” The rate of the first-attempt and total success, mean attempts to success, mean time to success, and incidence of complications (hematomas) were extracted. Data analysis was performed with RevMan 5.3.5. Results From 7 relevant studies, 558 radial artery catheterizations were enrolled, including 274 ultrasound-guided and 284 palpation catheterizations. The ultrasound-guided technique could significantly improve the rate of first-attempt and total success (RR 1.78, 95% CI 1.46 to 2.18, P < 0.00001; RR 1.33; 95% CI 1.20 to 1.48; P < 0.00001). However, there was significant heterogeneity for the total success rate among the included studies (I 2 = 67%). The ultrasound-guided radial artery catheterization was also associated with less mean attempts and mean time to success (WMD − 1.13, 95% CI − 1.58 to − 0.69; WMD − 72.97 s, 95% CI − 134.41 to − 11.52) and lower incidence of the hematomas (RR 0.17, 95% CI 0.07 to 0.41). Conclusions The use of the ultrasound-guided technique could improve the success rate of radial arterial catheterization and reduce the incidence of hematomas in pediatric patients. However, the results should be interpreted cautiously due to the heterogeneity among the studies.